Aplikasi Survei Kepuasan Peserta Diklat Berbasis Mobile Untuk Meningkatkan Pelayanan Diklat - Triase; Manurung, Liza Alzahra; Atsil, Rayhan Alpatih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Balai Diklat Keuangan Medan There is an Organizing and Learning sector which is tasked with carrying out learning related to State finances, facilitating the implementation of the Learning system and facilitating technical support for implementing learning needs analysis, learning evaluation, certification and competency tests as well as providing assistance services for implementing knowledge processes and learning organizations in the work area of the Financial Education and Training Center. This research was created to create a mobile-based training participant satisfaction survey system to improve training services. The aim is to improve training services that can be accessed easily by training participants. With the survey application, participant satisfaction data can be accessed and analyzed in real-time and this application makes the work of organizers easier in calculating satisfaction surveys and can provide data to the head of the Financial Training Center quickly. By using the waterfall method with Likert Scale calculations, this research produces an efficient information system through the stages of needs analysis, design, implementation, testing, maintenance and Likert scale calculations. The results obtained from this research are that the participant satisfaction survey application can make it easier for organizers to calculate survey results and make it easier for offices to improve office quality quickly.